Modernisation of the higher education system in the context of European integration - Svynarenko, D. (Економічний вісник Донбасу, 2025)
The article analyses the challenges and priorities of modernising Ukraine’s higher education (HE) system in the context of European integration. It provides an overview of educational transformation processes driven by both internal factors and external ones. Strategic approaches to modernisation implemented in countries of the European Union (EU) are identified, including digital, internationalisation, inclusive, innovative, communication-based, regional and sustainable development strategies. A typology of these strategies is provided, along with generalised examples of effective national practices. Special attention is given to approaches to internationalisation strategies, which encompass mechanisms for integrating higher education institutions (HEIs) into the global educational area and transnational research networks. A conceptual scientific-methodological approach to modernising Ukraine’s HE system is proposed, consisting of sequential stages: analytical-diagnostic, strategic-conceptual, normative-institutional, technological-innovative, social-partnership, educationalcultural and monitoring-evaluative. This model ensures the integrity and consistency of transformational changes in accordance with European standards and enables the adaptation of global practices to the local context. It is demonstrated that the modernisation of HE is not a mechanical process of borrowing but requires deep cultural and institutional assimilation of new concepts and practices. The implementation of the proposed approach will contribute to improving the quality of educational services, strengthening the innovative capacity of universities, enhancing their international attractiveness and forming a flexible and resilient educational system capable of functioning effectively under European integration conditions. У статті аналізуються виклики та пріоритети модернізації системи вищої освіти (ВО) України в контексті європейської інтеграції. Вона надає огляд процесів трансформації освіти, зумовлених як внутрішніми, так і зовнішніми факторами. Визначено стратегічні підходи до модернізації, що реалізуються в країнах Європейського Союзу (ЄС), включаючи цифрові, інтернаціоналізаційні, інклюзивні, інноваційні, комунікаційно-орієнтовані, регіональні та стратегії сталого розвитку. Наведено типологію цих стратегій, а також узагальнені приклади ефективних національних практик. Особлива увага приділяється підходам до стратегій інтернаціоналізації, які охоплюють механізми інтеграції вищих навчальних закладів (ВНЗ) у світовий освітній простір та транснаціональні дослідницькі мережі. Запропоновано концептуальний науково-методологічний підхід до модернізації системи вищої освіти України, що складається з послідовних етапів: аналітико-діагностичного, стратегічно-концептуального, нормативно-інституційного, технологічно-інноваційного, соціально-партнерського, освітньо-культурного та моніторингово-оцінювального. Ця модель забезпечує цілісність та узгодженість трансформаційних змін відповідно до європейських стандартів та дає змогу адаптувати світові практики до місцевого контексту. Показано, що модернізація вищої освіти не є механічним процесом запозичення, а вимагає глибокого культурного та інституційного засвоєння нових концепцій та практик. Реалізація запропонованого підходу сприятиме підвищенню якості освітніх послуг, зміцненню інноваційного потенціалу університетів, підвищенню їхньої міжнародної привабливості та формуванню гнучкої та стійкої освітньої системи, здатної ефективно функціонувати в умовах європейської інтеграції.